A Systematic Review of Treatment Interventions for Individuals With Intellectual Disability and Trauma Symptoms: A Review of the Recent Literature. (April 2022) - Byrne, Gary
Individuals with intellectual disabilities (IDs) are at increased susceptibility to adverse life experiences and trauma sequelae. There is a disparate range of therapeutic interventions for post-traumatic stress disorder (PTSD) and associated symptoms. This systematic review aimed to appraise the effectiveness of both cognitive behavioral therapy (CBT) and eye movement desensitization and reprocessing (EMDR) for PTSD and associated symptoms for both adults and children with mild, moderate, or severe intellectual delay. A systematic search, in line with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, of the PsychInfo, PubMed, Cochrane Database of Systematic Reviews, and MEDLINE databases were performed, and all relevant articles published between 2010 and March 2020 were included. A total of 11 articles were included, eight that focused on EMDR and three on CBT. The methodological quality of many of these articles was generally weak. Tentative findings suggest that EMDR and CBT are both acceptable and feasible treatment options among adults and children with varying levels of intellectual delay, but no firm conclusions can be drawn regarding effectiveness due to small sample sizes, lack of standardized assessment, and a paucity of methodological rigorous treatment designs. This review highlights the continued use of therapeutic approaches with clients presenting with IDs and PTSD. It adds to the extant literature by providing an expansive and broad overview of the current effectiveness of both EMDR and CBT. Further high-quality research is needed to provide more conclusive findings regarding treatment effectiveness and modifications to treatment needed with this population.